Parenting and Adolescents’ Self-Esteem: The Portuguese Context - Rodrigues, Yara (2013)
This study analyzes the relationships between parenting styles and adolescent’s psychosocial adjustment (self-esteem) in the Portuguese culture. The sample was of 517 adolescents, 214 males (41.39 %), and aged 11 to 18 years. We used the Parental Socialization Scale (ESPA29) to assess the parenting styles (authoritative, authoritarian, indulgent and negligent), and the Multidimensional Self-esteem Scale Form-5 (AF5) that assesses five dimensions of self-esteem: academic, social, emotional, family and physical. Results from this study indicate that adolescents from indulgent families scored equal to or even better than those from authoritative families in some indicators of psychosocial adjustment, in Portuguese adolescents. These results suggest that authoritative parenting is not associated with optimum self-esteem in Portugal. The study refers to the need for further research, taking account new contexts and cultures.